Long-Term Remission With Low-Dose Rituximab in Myasthenia Gravis: A Retrospective Study. Issue 1 (September 2022) - Castiglione, Juan I.; Rivero, Alberto D.; Barroso, Fabio; Brand, Patricio; Lautre, Andrea; Kohler, Alejandro A.
Abstract: Objetive: Rituximab (RTX) is a therapeutic option, for patients with myasthenia gravis (MG) not responding to conventional immunosuppressive treatment. In this cohort, we evaluated long-term efficacy of RTX in the treatment of refractory generalized MG. Methods: A retrospective study was performed in adult patients with refractory generalized MG and at least 24 months of follow-up, between January/2015 and October/2021. The Myasthenia Gravis Status and Treatment Intensity Score was used to assess outcomes, and CD19/CD20 + B-cell counts were monitored. Results: Sixteen patients with MG (8 antiacetylcholine receptor+ and 8 muscle-specific antikinase+; mean age 45.5 ± 16.2 years) treated with low-dose RTX protocols were included. CD19/CD20 levels remained undetectable 12 months after induction, and no new relapses were observed during follow-up. Conclusions: Low-dose RTX infusions were sufficient to achieve undetectable CD19/20 cell counts and sustained clinical remission. In low and middle-income countries, the impact of low-dose RTX therapy represents a paradigm shift in decision-making for long-term treatment.